2008
DOI: 10.1016/j.immuni.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transducer STAT5 Inhibits Plasmacytoid Dendritic Cell Development by Suppressing Transcription Factor IRF8

Abstract: The development of distinct dendritic cell (DC) subsets is regulated by cytokines. The ligand for the FMS-like tyrosine kinase 3 receptor (Flt3L) is necessary for plasmacytoid DC (pDC) and conventional DC (cDC) maturation. The cytokine GM-CSF inhibits Flt3L-driven pDC production while promoting cDC growth. We show that GM-CSF selectively utilized its signal transducer STAT5 to block Flt3L-dependent pDC development from the lineage-negative, Flt3+ (lin- Flt3+) bone-marrow subset. The signaling molecule STAT3, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
239
4
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(265 citation statements)
references
References 44 publications
20
239
4
2
Order By: Relevance
“…In addition, different cytokines appear to have varying effects on the development of specific DC subsets. For instance, GM-CSF favors the development of cDCs while inhibiting the development of pDCs, through a mechanism dependent upon activation of STAT5 [70]. In contrast, culturing bone marrow cells in M-CSF in combination with Flt3L has the opposite effect, favoring pDC development [51].…”
Section: Extracellular Cues Supporting DC Developmentmentioning
confidence: 99%
“…In addition, different cytokines appear to have varying effects on the development of specific DC subsets. For instance, GM-CSF favors the development of cDCs while inhibiting the development of pDCs, through a mechanism dependent upon activation of STAT5 [70]. In contrast, culturing bone marrow cells in M-CSF in combination with Flt3L has the opposite effect, favoring pDC development [51].…”
Section: Extracellular Cues Supporting DC Developmentmentioning
confidence: 99%
“…While STAT3 activation is not crucial for EPO-R activity (Menon et al, 2006), and its role in erythropoiesis is still not clear, it plays a prominent role in development and maturation 19 of DCs (Laouar et al, 2003;Tian et al, 2007). In that respect, STAT5 signaling is associated with inhibition of DC development (Esashi et al, 2008).…”
mentioning
confidence: 99%
“…As discussed above, it has been suggested that Stat5 activation suppresses the differentiation of pDC (Esashi et al, 2008). Stat5 deficient mice show slight reductions in lymphoid organ DC (Vremec et al, 1997;Esashi et al, 2008), echoing the phenotype of GM-CSFR deficient mice.…”
Section: Transcription Factors In DC Differentiation Signal Transducementioning
confidence: 89%
“…The addition of GM-CSF to FL stimulated cultures blocked pDC development from lin − Flt3 + progenitors, via an Stat5 dependent mechanism (Esashi et al, 2008). This abrogation of pDC development was shown to be the result of suppression of Irf8, a crucial transcription factor in pDC development, by Stat5.…”
Section: Gm-csfmentioning
confidence: 93%
See 1 more Smart Citation